Seroprevalence of genital Chlamydia trachomatis infection in women of reproductive age - Mahmud, NU; Hossain, MA; Nahar, K; Mahmud, C; Paul, SK; Ahmed, S; Haque, N; Kalam, A; Parveen, US (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 187-91. The abstract of this article is available on the PubMed website